A multiple‐criteria decision‐making approach for the evaluation of retail location - Burnaz, Sebnem; Topcu, Y. Ilker (Wiley, 2006)
AbstractThis study proposes an ANP‐based evaluation of retail locations. Authors acted as decision analysts and interacted with professionals in Turkish apparel retailing sector for acquiring their knowledge and expertise. As a result, evaluation criteria of the study were identified. These criteria are clustered into five groups: store, other retailers, shopping centre/business district, accessibility, and environmental. The relationship among criteria were assessed and a network was formed. ANP approach was then utilized in order to evaluate possible retail locations for the apparel stores. Besides global preferences of these alternatives, relative importance of the criteria was also revealed. Copyright © 2007 John Wiley & Sons, Ltd.